Chloranthus flavus (Chloranthaceae), a new species from Guangxi, China - Liu, De-Tuan; Cai, Lei; Chen, Gao (Phytotaxa, 2019)
Chloranthus flavus sp. nov., a new species from Guangxi Zhuang Autonomous Region in China, is described based on living organisms and type specimens. The new species is morphologically similar to Chloranthus nervosus Coll. et Hemsl. due to their similar flower and leaf characters. However, they can be easily distinguished by their habits, stems and color of stamen connectives. The main morphological features of the new species are described, and color photographs are provided.